ESSENTIALS OF BUSINESS ANALYTICS - CAMM D JEFFREY; JAMES J COCHARN; MICHEAL J FRY; JEFFREY W OHLMANN; DAVID R ANDERSON; DENNIS J SWEENEY; THOMAS A WILLIAMS (DELHI CENGAGE LEARNING INDIA PRIVATE LIMITED, 2019)
"Essentials of Business Analytics," co-authored by Jeffrey D. Camm, James J. Cochran, Michael J. Fry, Jeffrey W. Ohlmann, and David R. Anderson, serves as a foundational text for students and professionals seeking to understand and apply the principles of business analytics. The book provides a comprehensive overview of the three pillars of business analytics$1 (Bdescriptive, predictive, and prescriptive analytics$1 (Bequipping readers with the tools and techniques necessary to make informed,s
MBA
BUSINESS
Keywords: BUSINESS ANALYTICS; MANAGEMENT